Pendidikan Multikultural Dalam Membentuk Karakter Bangsa Melalui Pembelajaran IPS Di Sekolah Confucius Terpadu SD Mulia Bakti Purwokerto Kabupaten Banyumas - Tutuk Ningsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
The purpose of this study is to find and describe the multicultural education in forming the character of the nation through social sciences learning. The approach considered suitable for this type of research is qualitative. The results of this study obtained some informations, 1) Multicultural education in forming the character of the nation through social sciences learning at Integrated Confucius Elementary School Mulia Bakti Purwokerto has been done by adjusting subject matter of social sciences in each class, from class I to class V associated with multicultural education. 2) Multicultural education in the empowerment of school culture, social structure and education of equal / fair in forming the character of the nation through social sciences learning at Integrated Confucius Elementary School Mulia Bakti Purwokerto has been done by the teachers welcome their students coming every morning, the students shake hands and the teachers fix the students' uniforms and tidy up the hair sometimes. Greetings with smile and polite routinely is always getting used. In school there is no distinction, all students get the same recognition, whether they are Muslim or non-Muslim, they are included in every activity, break fasting togheter, feast day, Chinese New Year, and other activities. 3) Multicultural education can be seen from terms of solidarity, cooperation, tolerance, in forming the character of the nation through social sciences learning. The activity of teacher and student in the classroom as well as in schools is done together so that the differences from religion, tribe, culture are not visible in order to maintain cohesiveness in the classroom. In terms of solidarity, students play like students in other schools, they play without discriminating caused by their origins, they also exchange information about their daily religious activities and the good lessons of their religion.